Bacterial Diversity in House Dust: Characterization of a Core Indoor Microbiome - Thompson, Jonathan R.; Argyraki, Ariadne; Bashton, Matthew; Bramwell, Lindsay; Crown, Matthew; Hursthouse, Andrew S.; Jabeen, Khadija; Marinho Reis, Paula; Namdeo, Anil; Nelson, Andrew; Pearce, David A.; Potgieter-Vermaak, Sanja; et al. (Frontiers in Environmental Science, 2021)
Our indoor microbiome consists of a wide range of microbial taxa. Whilst many of these microbes are benign, some are beneficial, some harmful, yet our knowledge of the spatial heterogeneity of bacterial assemblages in our residential environment remains limited. To investigate the existence of a common core house dust bacterial microbiome we selected household vacuum dusts, collected through a citizen science approach, from homes across two bioclimatic regions (UK, Oceanic/Maritime and Greece, Mediterranean). Following the extraction of DNA from each dust sample, we targeted the bacterial 16S rRNA gene using Illumina NextSeq sequencing. PERMANOVA analysis of the microbial communities at family level grouped samples within their distinct bioclimatic region and SIMPER analysis at genus level identified the statistically significant taxa responsible for driving diversity between these groups. A ‘common to all’ core house dust microbiome consisted of Acinetobacter, Massalia, Rubellimicrobium, Sphingomonas and Staphylococcus; genera typically associated with human occupancy and common environmental sources. Additionally, a ‘unique location specific’ microbiome was identified, reflective of the bioclimatic region. The Greek dusts indicated a lower average diversity than the UK house dusts, with a high abundance of Rhizobaciacae in the Greek samples. Our study highlights citizen science as a powerful approach to access the indoor residential environment, at scale, and establishes the existence of a ‘core’ house dust microbiome independent of bioclimatic region.